2015
DOI: 10.4049/jimmunol.1401704
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: GPR35/CXCR8 Is the Receptor of the Mucosal Chemokine CXCL17

Abstract: Chemokines are chemotactic cytokines that direct the traffic of leukocytes and other cells in the body. Chemokines bind to G protein-coupled receptors (GPCRs) expressed on target cells to initiate signaling cascades and induce chemotaxis. Although the cognate receptors of most chemokines have been identified, the receptor for the mucosal chemokine CXCL17 is still undefined. Here we show that GPR35 is the receptor of CXCL17. GPR35 is expressed in mucosal tissues, in CXCL17-responsive monocytes, and in the THP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
161
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(177 citation statements)
references
References 34 publications
10
161
6
Order By: Relevance
“…This could be explained by decreased migration of T cells from LN and spleen to the CNS, for example, through altered expression of chemokine receptors. However, we did not find changes in the expression of GPR35, one of the proposed receptors for CXCL17 (data not shown). Lack of CD44 expression has also been correlated with a worse outcome of mice in the EAE model, possibly due to cytokine production associated with Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by decreased migration of T cells from LN and spleen to the CNS, for example, through altered expression of chemokine receptors. However, we did not find changes in the expression of GPR35, one of the proposed receptors for CXCL17 (data not shown). Lack of CD44 expression has also been correlated with a worse outcome of mice in the EAE model, possibly due to cytokine production associated with Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need to clarify the relevance of these reported effects of ligands at GPR35 and their significant species selectivity in future studies. It has been reported that GPR35 is expressed in CXCL17-responsive monocytes and in the THP-1 monocytoid cell line and may function as a novel chemokine receptor of the mucosal chemokine CXCL17 [33]. Thus, GPR35 function in macrophages/immune cells is pro-inflammatory, and there-fore, its loss in macrophages would be expected to reduce inflammation and promote intestinal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL17 is also expressed in malignancy: in hepatocellular carcinoma, CXCL17 was produced mainly by tumor-infiltrating neutrophils and occasionally by the tumor cells (4). The receptor of CXCL17 was recently detected as GPR35/CXCR8, which is expressed in mucosal tissues, including the gastrointestinal tract and lung (5). The ImmGen database indicated that GPR35 is expressed by macrophages, dendritic cells, and granulocytes (5).…”
mentioning
confidence: 99%
“…The receptor of CXCL17 was recently detected as GPR35/CXCR8, which is expressed in mucosal tissues, including the gastrointestinal tract and lung (5). The ImmGen database indicated that GPR35 is expressed by macrophages, dendritic cells, and granulocytes (5).…”
mentioning
confidence: 99%